FREQUENCY AND STRUCTURE OF IMMEDIATE POSTOPERATIVE COMPLICATIONS IN CHILDREN WITH HIRSHPRUNG’S DISEASE (International Journal of Scientific Pediatrics, 2023)
Summary. To date, more and more common in Hirschsprung's disease is becoming a radical one-stage surgical treatment using minimally invasive methods of surgical intervention. Modern surgical methods for the treatment of Hirschsprung's disease in newborns and young children can reduce mortality and improve outcomes. Purpose of the study. To study the indicators of functional activity and quality of life in children with Hirschsprung's disease operated on by the De La Torre-Ortega method. Material and research methods. The study included 21 children operated on for Hirschsprung's disease at the clinical bases of the Department of Pediatric Surgery of the Andijan State Medical Institute. The patients were aged 2 to 18 years. 4 (19.04%) patients were admitted to the clinic in the stage of decompensation, 12 (57.14%) - in the stage of subcompensation, 5 (23.8%) - in the stage of compensation. In 13 (61.9%) children, an improved technique of the De La Torre-Ortega operation was performed, and 8 (38.1%) children underwent transanal resection of the colon according to the classical Soave-Lenyushkin technique.The article presents the results of studying the functional activity and quality of life of children with Hirschsprung's disease operated on by the improved De La Torre-Ortega method and the classical Soave-Lenyushkin method. The quality of life of operated children was assessed using the adapted PedsQL™4.0 scale, which includes a total of 21 questions assessing physical, emotional, social and role functioning. An analysis of the quality of life of children with Hirschsprung's disease showed a significant increase in indicators on all scales when performing an improved technique of the De La Torre-Ortega operation up to 84.1-92.3% in relation to the group of healthy children with a change in the total score from 52.8±10 .0 to 70.4±6.4 (t=6.79; p
Keywords: Hirschsprung's disease; quality of life; functional activity; children